Single-phase proton- and electron-conducting Ag-organic coordination polymers for efficient CO2 electroreduction. Issue 6 (18th January 2022) - Zou, Yingbing; Zhan, Tingting; Yang, Ying; Fan, Zhiwen; Li, Yunbin; Zhang, Yongfan; Ma, Xiuling; Chen, Qianhuo; Xiang, Shengchang; Zhang, Zhangjing
Abstract : Two single-phase MOCPs with different electron and proton conductivities were used for the electrocatalytic CO2 RR. Abstract : Here a single-phase proton- and electron-conducting metal–organic coordination polymer (MOCP) electrocatalyst for the CO2 reduction reaction (CO2 RR) was constructed by using Ag as the metal center and 1 H -1, 2, 3-triazole (Tz) as the ligand. To evaluate the effects of tuning the conductivity of Ag-MOCP on CO2 RR performances, another Ag-MOCP was selected for comparison by using 1 H -benzotriazole (Btz) as the ligand. The proton conductivity for Ag-MOCP-Tz is 2.3 × 10 −7 S cm −1, 70-fold that for Ag-MOCP-Btz with 3.3 × 10 −9 S cm −1 at 25 °C and 98% RH. And the electron conductivity of Ag-MOCP-Tz (3.57 × 10 −7 S cm −1 ) is 120 times that of Ag-MOCP-Btz (2.96 × 10 −9 S cm −1 ) at 25 °C. Meanwhile the FECO of Ag-MOCP-Tz is 85.9% at −0.98 V vs. RHE, which is better than that of Ag-MOCP-Btz with 65.4%.